Mobile Devices in Social Contexts - Heidi Tscherning (Copenhagen Business School (CBS), 2011)
The development of mobile devices has occurred with unprecedented pace since the late nineties, and the increase of generic services has proliferated in most developed countries, driven by the expanding technological capabilities and performance of mobile platforms. This dissertation investigates how consumer objectives, orientation, and behavior can aid in explaining the adoption and use of a new type of mobile devices: “app phones”. This dissertation focuses its effort on two focal influences of adoption and use; social influences and competing forces. Through a qualitative case study and field study this dissertation explores early adoption and use of iPhones. The case study is a one-shot cross-sectional case study that investigates five individuals, related through the same social network, and their decision to adopt an iPhone prior to its release in Denmark. This adoption decision engenders high switching costs as adopters lack references to imitate and need skills to unlock and jailbreak their iPhones to make them work on Danish networks. The specific purpose of the case study is to explore how social influences impact mobile users' early adoption decisions, as it is well known in the literature that people with similar characteristics, tastes, and beliefs often associate in the same social networks and, hence, influence each other. The field study is cross-sectional with multiple snapshots and explores fifteen individuals part of the same university study, who receives an iPhone for a period of seven months short after its release in Denmark. The specific purpose of the field study is to explore how competing forces of iPhone usage influence assimilation, i.e. the degree to which the iPhone is used, over time. The dissertation, furthermore, contains a systematic literature review. The main contribution of this dissertation is reported through four articles and is directed at both academic researchers and practitioners. The study emphasizes the importance of social influences and competing forces in the investigation of adoption and use of certain mobile devices.
hdl:10398/8342
Keywords: 650